Improving Pulmonary Tuberculosis Treatment Adherence: The role of patient knowledge in Cirebon, West Java, Indonesia - Marfuati, Sri; Fitriani, Hikmah; Weni, Mustika; Riawan, Firanda Putri (GHMJ (Global Health Management Journal), 2024)
Background: With 10 million cases around the world, pulmonary tuberculosis (TB) has been classified as a highly contagious disease and mostly affecting low and middle countries. Having the second highest incident cases in West Java of Indonesia, Cirebon becomes a challenging city in order to reduce the number of TB cases in the country. Aims: This study aims to identify the patients’ knowledge and treatment phases, and how the two factors encourage patients to comply with their medication. Methods :  This cross-sectional observational study was conducted among 91 new pulmonary tuberculosis patients at the Cirebon City Community Lung Health Centre, selected using random sampling. Not only respondent characteristics, but also data on the patients' knowledge levels, treatment phases, and medication adherence were collected using a questionnaire and medical records. To assess the relationship between these variables, the collected data was then analyzed using the Spearman Correlation test. Ethical clearance was obtained from the Health Research Ethics Commission, and informed consent was gathered from all participants. Results: This study reveals the most updated characteristics of the Tuberculosis patients at the Cirebon City Community Lung Health Center aged 15-64 years old with treatment duration ranged 1-6 months. The majority have insufficient knowledge about tuberculosis (45.1%), and 75.8% of patients adhered to their prescribed medication regimen, regardless of their knowledge level. The data indicates a significant positive correlation between knowledge level and medication adherence (p = 0.015), with 95% of patients with good knowledge adhering to treatment compared to only 34% with poor knowledge. Furthermore, there is a significant relationship between adherence and treatment duration (p = 0.002), as 85% of patients who adhered to treatment did so for more than two months. Conclusion: The study shows that patients with better knowledge of tuberculosis are more likely to stick to their medication, which also leads to longer treatment durations. Given the high incidence of TB in the region, these findings suggest the need for targeted educational programs to enhance patients' understanding of TB, thereby improving adherence to treatment protocols. Received: 20 May 2024, Reviewed: 09 June 2024, Revised: 26 August 2024, Accepted: 30 August 2024.